2014
DOI: 10.1212/wnl.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between adolescent obesity and HLA risk genes in the etiology of multiple sclerosis

Abstract: Objective:We investigated potential interactions between human leukocyte antigen (HLA) genotype and body mass index (BMI) status in relation to the risk of developing multiple sclerosis (MS).Methods:We used 2 case-control studies, one with incident cases (1,510 cases, 2,017 controls) and one with prevalent cases (937 cases, 609 controls). Subjects with different genotypes and BMI were compared with regard to incidence of MS by calculating odds ratios (ORs) with 95% confidence intervals (CIs) employing logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(167 citation statements)
references
References 33 publications
10
141
3
8
Order By: Relevance
“…Several studies have shown that obesity in the adolescent years, but not the adult years, is a risk factor for MS 7, 8, 9, 10, 11. This study further emphasizes this trend and confirms a role of obesity in development of pediatric‐onset MS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Several studies have shown that obesity in the adolescent years, but not the adult years, is a risk factor for MS 7, 8, 9, 10, 11. This study further emphasizes this trend and confirms a role of obesity in development of pediatric‐onset MS.…”
Section: Discussionsupporting
confidence: 80%
“…In parallel, there is increasing evidence that obesity during adolescence is associated with a higher risk of MS in adults 7, 8, 9, 10, 11. In children, one study found an effect of obesity in girls but not in boys;12 however, a smaller number of male cases may have limited the ability to detect an effect.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue produces and releases a variety of pro-inflammatory cytokines, including leptin, which promotes Th1 responses and reduces regulatory T-cell activity. Researchers have recently published data from a new study comprising two large populations of MS patients and controls, confirming the previously described association between obesity in early life and increased risk of developing MS [4]. Using a Swedish population-based case-control study as well as an American case-control study, the authors observed striking interactions between body mass index status and human leukocyte antigen (HLA)-DRB1*15 allele, the gene most strongly associated with MS, with regards to MS risk.…”
Section: Reviewsupporting
confidence: 69%
“…A couples of studies showed that the presence of HLA-DRB1*15 and absence of HLA-A*02 in obese or smoking patients increases the risk of MS (OR= 16.2 and 13.5, respectively), while the absence of those genotype correlated with a much lower risk (OR=3.7 and 1.4, respectively) [76,77]. If anything, this indicates that the presence of HLA-A*02 may confer resistance to provocative stimulation through obesity or smoking in MS. HLA-C*05 belongs to group 2 of HLA-C alleles that interact with killer immunoglobulin-like receptors (KIR) [78].…”
Section: Cd8+ T-cellsmentioning
confidence: 99%